Three topics to the evolution of the environmetal impact assessment - Verna Coronado, Vito (2013)
The paper identifies three topics in order to evaluate the improvements in the regulation of the National System of EnvironmentalImpact Assessment, looking to benefit the people’s trust in the environmental certification. The first one consists in the gradual transition from the prevention paradigm to the integration one, as the purpose of the different instruments that compose the system; the second involves the enrichment in the evaluation of the Environmental Impact Study (EIS), by incorporating the scoping phase; and the third involves adopting additional measures that reinforce the independence of the teams in charge of the elaboration and evaluation of the EIS.